Universum, logos and res species - Barczak, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2007)
The paper presents a discussion on the fundamental problems of higher education institutions in Poland after 1990. The author points the main features of changes, but his concern is on threats to university education. Most of these threats come from commercialization and standardization of higher education
Argumenta Oeconomica, 2007, No 1-2 (19), s. 43-48
Keywords: higher education; Bologna process